Intensity-modulated lateral microdisplacement sensor enabled by cleaved tapered fiber tips - Liu, Yan; Wang, Weiwei; Li, Yang (Optical engineering, 2017)
A lateral microdisplacement sensor based on tapered fiber tips, which is suitable for measuring lateral displacement with high sensitivity, is proposed. A jacket-off single-mode fiber (SMF) is tapered down to tens of microns and then cleaved in the middle of the waist region to get two identical tapered fiber tips. The lateral microdisplacement can be measured by monitoring the transmission intensity of a tip-tip structure. The beam propagation characteristics of such tapered fiber tips with different waist diameters are analyzed in detail. The tip-tip structure, together with the structure composed by one tip and one cleaved SMF, is investigated both experimentally and numerically. Experimental and numerical results show that this kind of lateral microdisplacement sensing structure can provide remarkable performance. A sensitivity of about −1.0  dB/μm with a measuring range of 28  μm is obtained experimentally.